Earnings Growth and Employment Creation : An Assessment of World Bank Support in Three Middle-Income Countries - Independent Evaluation Group (World Bank, Washington, DC, 2016)
The primary aim of this evaluation is to develop lessons from the Bank’s experience in the three selected countries of Columbia, Tunisia, and Turkey regarding assistance aimed at employment creation and earnings growth. The evaluation focuses on employment creation and earnings growth because these have a strong bearing on the extent to which the central objective of poverty reduction is achieved. The evaluation assesses the impact of the Bank’s assistance on employment outcomes and focuses on relevance and effectiveness of Bank engagement on employment issues. Two findings in connection with outcomes across the three countries are highlighted. First, progress in economic growth and earnings was better than progress in employment and unemployment. Second, although the availability of statistics on employment and earnings outcomes has improved, there are still significant deficiencies. These findings suggest a number of implications for Bank support during the global unemployment crisis as follows: (a) deploy the Bank’s integrative capability to provide support in the different areas affecting employment outcomes; (b) focus on the classical, cyclical, and structural sources of unemployment; (c) update and improve employment and earnings data; (d) adjust programs to emphasize support with strong employment earnings effects;(e)advise countries on affordable fiscal stimuli; (f) support the development of unemployment insurance mechanisms; and (g) develop strategies to advance job flexibility and worker protection. IEG recommends that the Bank continue focusing on advice and projects to improve coverage and quality.